Photocatalytic Performance of Fe2O3 Modified TiO2 Catalyst Towards the Degradation of Rhodamine 6G - CHUAN, FU; TINGZHEN, LI; JUNSHENG, QI; JIE, PAN; CONG, CHENG (Asian Journal of Chemistry, 2010)
Fe2O3-TiO2 coatings were prepared on glass slide substrates using sol-gel method. The phase structure, thermal microstructure and surface properties of the coatings were respectively characterized by using X-ray diffractometry, scanning electron microscopy (SEM) and UV-Vis diffuse reflectance spectroscopy. The Fe2O3-TiO2 photocatalyst shows obvious red-shift compared with pure TiO2 by DRS, absorbance in the visible range of the Fe2O3-TiO2 samples increases with the increase of the amount of Fe2O3 loaded. The photocatalytic activity had been validated by the photocatalytic degradation of rhodamine 6G. The result showed that 15 wt % Fe2O3 modified TiO2 film is the optimal photocatalyst to degradation. The removal rate of TOC indicated that a lower pH value was beneficial to the mineralization of rhodamine 6G.